Aplikasi Survei Berbasis Android - Eric Prabowo Cundomanik; Lily Puspa Dewi; Justinus Andjarwirawan (Jurnal Infra, 2016)
Survey process in the field needs surveyor to writedown data manually on a paper. Manual data recording process will later be repeated to save it in the computer for a digital data. This process increases the possibility to have an error in the data input step from a handwritten data. Furthermore, there is a need to turn the survey data into a processed data for a decision making purpose by the survey administrator.Android is chosen as the mobile device platform in this thesis, because it is the most used platform in smartphones. Also, it answers the need of a surveyor in the field to easily carry the survey data. Server application uses Node.js framework to minimalize data process between platforms.There are two applications as the result, which are administrator web application and surveyor Android-based application. Web application is for creating, viewing, changing, deleting, and processing question and survey result data. Android-based application is to be used by specific surveyor in the field for answering many kinds of question types that is created in the web application.